A Numerical Study of Atmospheric Perturbations Induced by Heat From a Wildland Fire: Sensitivity to Vertical Canopy Structure and Heat Source Strength. Issue 5 (7th March 2018) - Kiefer, Michael T.; Zhong, Shiyuan; Heilman, Warren E.; Charney, Joseph J.; Bian, Xindi
Abstract: An improved understanding of atmospheric perturbations within and above a forest during a wildland fire has relevance to many aspects of wildland fires including fire spread, smoke transport and dispersion, and tree mortality. In this study, the ARPS‐CANOPY model, a version of the Advanced Regional Prediction System (ARPS) model with a canopy parameterization, is utilized in a series of idealized numerical experiments to investigate the influence of vertical canopy structure on the atmospheric response to a stationary sensible heat flux at the ground ("fire heat flux"), broadly consistent in magnitude with the sensible heat flux from a low‐intensity surface fire. Five vertical canopy structures are combined with five fire heat flux magnitudes to yield a matrix of 25 simulations. Analyses of the fire‐heat‐flux‐perturbed u component of the wind, vertical velocity, kinetic energy, and temperature show that the spatial pattern and magnitude of the perturbations are sensitive to vertical canopy structure. Both vertical velocity and kinetic energy exhibit an increasing trend with increasing fire heat flux that is stronger for cases with some amount of overstory vegetation than cases with exclusively understory vegetation. A weaker trend in cases with exclusively understory vegetation indicates a damping of the atmospheric response to the sensible heat from a surface fire when vegetation is most concentrated near the surface. More generally, the results presented in this study suggest that canopy morphology should be considered when applying the results of a fire‐atmosphere interaction study conducted in one type of forest to other forests with different canopy structures. Key Points: Perturbation of the atmosphere by sensible heat from a surface fire is sensitive to vertical canopy structure Caution is suggested when extrapolating study findings across forests with different canopy structure